Monitoring of transplanted human Mesenchymal Stem Cells from Wharton’s Jelly in xenogeneic systems in vivo - Kovalchuk, M.V.; Shuvalova, N.S.; Pokholenko, I.O.; Dragulyan, M.V.; Gulko, T.P.; Deryabina, O.G.; Kordium, V.A. (Вiopolymers and Cell, 2015)
Mesenchymal stem cells (MSCs) are ideal candidates for cell-based therapy aimed at tissue repair and immunomodulation. Aim. to study the survival of transplanted human MSCs from umbilical cord Wharton’s Jelly (hWJ-MSCs) in the animal model of experimental osteoarthritis (OA) in rats after injecting cells into a knee joint and to explore the effect of collagen scaffold on the cell survival in vivo. Methods. MSC isolation and cultivation in vitro. Immunological phenotyping of propagated hWJ-MSCs was performed by flow cytometry. The retention of transplanted cells was studied by the PCR revealing of human specific sequences in genomic DNA extracted from animal tissues. Results. hWJ-MSCs, both individual and grown on scaffold, were used and it was shown by PCR that human alpha-satellite DNA was detected on the first day in the immunocompetent OA animals inside the injured knee joint. In the collagen matrix (in the model of subcutaneous implantation) human alpha-satellite DNA was detected on the 5th day but was not detected on the 12th day. Conclusions. According to the PCR results, hWJ-MSCs survived in the OA animal model for a short period. Collagenic scaffold increased the residence time of donor cells in the recipients. hWJ-MSCs may be considered as a perspective cell source for the treatment of OA in human. Мезенхимальные стволовые клетки (МСК) являются идеальными кандидатами для восстановление тканей и иммуномодуляции при клеточной терапии. Цель. Изучить выживание трансплантированных МСК Вартонового студня пуповины человека (МСК-ВС) на модели экспериментального остеоартроза у крыс (введение клеток в коленный сустав), и исследовать влияние коллагенового матрикса на выживание МСК-ВС in vivo. Методы. Выделение и культивирование МСК-ВС in vitro. Иммунологическое фенотипирование мультиплицированных МСК-ВС проведено с помощью проточной цитофлуорометрии. Сохранение трансплантированных клеток изучали с помощью ПЦР, выявляющей специфические для человека последовательности в геномной ДНК, изолированной из тканей животных. Результы. Исследование индивидуальних и выращенные на матриксе МСК-ВС, с помощью ПЦР, показало, что альфа-сателлитная ДНК человека детектировалась в первые сутки у иммунокомпетентных животных в поврежденном суставе. В коллагеновом матриксе (в модели подкожной имплантации) ДНК человека была обнаружена на 5, но не детектировалась на 12 сутки. Выводы. По результатам ПЦР МСК-ВС выживали у животных с остеоартритом в течение короткого периода. Коллагеновый матрикс увеличивал продолжительность пребывания МСК-ВС у реципиентов. МСК-ВС могут рассматриваться как перспективный источник клеток для лечения остеоартрита у человека. Мезенхімальні стовбурові клітини (МСК) є ідеальними кандидатами для відновлення тканин та імуномодуляції при клітинній терапії. Мета. Вивчити виживання трансплантованих МСК Вартанового студню пуповини людини (МСК-ВС) на моделі експериментального остеоартрозу у щурів (введення клітин в колінний суглоб), та дослідити вплив коллагенового матриксу на виживання МСК-ВС in vivo. Методи. Виділення і культивування МСК-ВС in vitro. Імунологічне фенотипування мультиплікованих МСК-ВС проведено за допомогою проточної цитофлуорометрії. Збереження трансплантованих клітин вивчали за допомогою ПЛР, що виявляє специфічні для людини послідовності в геномній ДНК, ізольованій з тканин тварин. Результи. Використано індивідуальні та вирощені на матриксі МСК-ВС, ПЛР показано, що альфа-сателітна ДНК людини в пошкодженому суглобі у імунокомпетентних травмованих тварин виявлялась за добу. У колагеновому матриксі (в моделі підшкірної імплантації) ДНК людини була виявлена на 5, але не детектувалась на 12 добу. Висновки. За результатами ПЛР МСК-ВС виживали у тварин з остеоартрітом протягом нетривалого часу. Колагеновий матрикс збільшував тривалість перебування МСК-ВС у реципієнтів. МСК-ВС можуть розглядатися як перспективне джерело клітин для лікування остеоартриту у людини.